Tennis Elbow Treatment (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Lateral epicondylitis, popularly known as tennis elbow or simply tennis elbow, is an excess ailment caused by a mechanical overloading of the typical extension muscle near the beginning of the extensor carpus radialis brevis (ECRB) tendon.Chronic discomfort in the left epicondyle within the elbow is a rather frequent ailment, especially in athletes in tennis and workers. Chronic pathologic alterations in the ligament roots are correlated with severe discomfort, but the root causes still unknown.Many treatments have been proposed to alleviate the symptoms caused by the disease (limited movement, pain), as most clinical studies have concluded that there are good results for physical therapy accompanied by reducing the activities that provoke symptoms attacks. Physical therapy falls under the category of non-surgical treatment, as well as administering non-steroidal anti-inflammatory drugs, local steroid injections, and many other treatments, as it is preferable to limit surgical treatment to specific indications. This research sheds light on the many different treatments in addition to proposing an algorithm for the initial management.